Support for Strategic Voting Campaigns: Evidence from a~Survey Experiment During the German General Election of 2021 - Michael Jankowski (Politische Vierteljahresschrift, 2023)
Although strategic voting is common in the first tier of the German electoral system, large-scale campaigns designed to foster strategic voting have rarely been observed in Germany. This changed in the General Election of 2021 when the left-wing organization Campact ran campaigns in several electoral districts supporting the most promising left-wing candidate in order to impede the election of a~more right-wing candidate. Especially, Campact's campaign in favor of the SPD candidate Frank Ullrich, with the goal of impeding the election of the controversial CDU candidate Hans-Georg Maaßen, received much public attention. Drawing on this case as an example, I address the question of how Green voters evaluate such campaigns. To do so, I conducted a~survey experiment in which different information about the campaign of Campact is provided to Green voters. I find that providing more information about the German electoral system does not increase support for the campaign. However, Green voters react to a~party cue, i.e., they become more favorable towards the campaign when they know that the Green Party supported the campaign.
Keywords: 320; Electoral Systems; Public Opinion; Election Campaigns; Survey Experiment; Green voters; Wahlsysteme; Öffentliche Meinung; Wahlkampagnen; Umfrageexperiment; Grüne Wähler